2023
DOI: 10.1186/s42234-023-00112-7
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinting patient-derived induced pluripotent stem cell models of Alzheimer’s disease using a smart bioink

Abstract: Background Alzheimer’s disease (AD), a progressive neurodegenerative disorder, is becoming increasingly prevalent as our population ages. It is characterized by the buildup of amyloid beta plaques and neurofibrillary tangles containing hyperphosphorylated-tau. The current treatments for AD do not prevent the long-term progression of the disease and pre-clinical models often do not accurately represent its complexity. Bioprinting combines cells and biomaterials to create 3D structures that repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Other studies have also confirmed the suitability of this technique to generate models of Alzheimer's and Parkinson's disease. Benwood et al differentiated healthy and patient-derived iPSCs into NPCs, and incorporated these cells into dome-shaped constructs that promoted the differentiation of NPCs into basal forebrainresembling cholinergic neurons (BFCN), the first cell type affected in the progression of Alzheimer's disease [186]. With regard to the application of this technology in the production of models of Parkinson's disease, Abdelrahman et al reported the fabrication of a peptide-based model that maintained the activity of encapsulated dopaminergic neurons for more than one month.…”
Section: Modeling Neurodegenerationmentioning
confidence: 99%
“…Other studies have also confirmed the suitability of this technique to generate models of Alzheimer's and Parkinson's disease. Benwood et al differentiated healthy and patient-derived iPSCs into NPCs, and incorporated these cells into dome-shaped constructs that promoted the differentiation of NPCs into basal forebrainresembling cholinergic neurons (BFCN), the first cell type affected in the progression of Alzheimer's disease [186]. With regard to the application of this technology in the production of models of Parkinson's disease, Abdelrahman et al reported the fabrication of a peptide-based model that maintained the activity of encapsulated dopaminergic neurons for more than one month.…”
Section: Modeling Neurodegenerationmentioning
confidence: 99%
“…44 Various cell types have been previously used in 3D bioprinting, and Table 3 below shows a summary of the some of the typically used cells and bioinks in relation to its target tissue model. [45][46][47][48][49][50][51][52][53] Bioink selection 3D bioprinting depends significantly on bioinks, biomaterials, and cells for generating 3D cultures, with these bioinks necessitating functionality and biocompatibility to replicate the properties of living tissues. 10 In selecting the appropriate bioink for 3D bioprinting, it is essential to be familiar with their general functions, which are typically categorized into four: structural, functional, sacrificial, and support.…”
Section: Cell Type Selectionmentioning
confidence: 99%
“…distilled water, ammonium hydroxide solution, lithium bromide solution, RPMI 1640 medium, deionized water, McCoy's 5A medium) following manufacturer's instructions. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Afterwards, if the bioink is multicomponent, an additional material is mixed into the solution to obtain the target concentration. 59,61 Generally, multicomponent bio-inks are favored over single biomaterial-based bioinks because they can maintain maximal cell viability by mitigating the varying toxic effects each biomaterial may have on different cells.…”
Section: Supportmentioning
confidence: 99%
See 1 more Smart Citation